The Importance of Fine Arts Classes in Developing Students’ Artistic Thinking - Khalilov R.Sh.; Z.Tursunboyeva (European International Journal of Pedagogics, 2026)
This article analyzes the role and significance of fine arts classes in the development of artistic thinking among students in higher education institutions. Through fine arts education, students’ aesthetic taste, imaginative thinking, creative abilities, and independent thinking skills are developed and theoretically substantiated. The article also highlights the pedagogical possibilities of developing artistic thinking through practical exercises, composition, painting, and graphic art. The research results show that effective organization of fine arts classes contributes to the enhancement of students’ creative activity.